2009
DOI: 10.1080/02705060.2009.9664336
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Fixation byAnabaena fertilissimaunder Elevated CO2and Temperature

Abstract: We studied the growth of Anabaena fertilissima under graded C 0 2 and temperature conditions to assess its suitability as a C02 scavenger for carbon recycling. A. fertilissima reached maximum growth at 6% C02, but growth declined above this C 0 2 level; yet, at no C 0 2 concentration growth was less than that at ambient C02. High temperature (>30°C) reduced growth of the cyanobacterium, but presence of elevated (6%) C02 lessened the intensity of that reduced growth. High temperature also reduced biomass, pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…Alternatively, increased CO 2 may have directly increased N 2 fixation by cyanobacteria in the fern leaf cavities. This is in line with previous studies wherein, firstly, nitrogenase activity increased 2.6‐fold when the cyanobacterium Anabaena fertilissima was grown at 60 000 ppm CO 2 compared to ambient CO 2 and, secondly, 900 ppm CO 2 increased nitrogen fixation rates 1.5‐ to 3‐fold compared to ambient CO 2 in the marine cyanobacterium Trichodesmium . Still, experiments carried out here did not rule out enhanced nitrate uptake at elevated CO 2 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Alternatively, increased CO 2 may have directly increased N 2 fixation by cyanobacteria in the fern leaf cavities. This is in line with previous studies wherein, firstly, nitrogenase activity increased 2.6‐fold when the cyanobacterium Anabaena fertilissima was grown at 60 000 ppm CO 2 compared to ambient CO 2 and, secondly, 900 ppm CO 2 increased nitrogen fixation rates 1.5‐ to 3‐fold compared to ambient CO 2 in the marine cyanobacterium Trichodesmium . Still, experiments carried out here did not rule out enhanced nitrate uptake at elevated CO 2 .…”
Section: Resultssupporting
confidence: 93%
“…This is in line with previous studies wherein, firstly, nitrogenase activity increased 2.6-fold when the cyanobacterium Anabaena fertilissima was grown at 60 000 ppm CO 2 compared to ambient CO 2 and, secondly, 900 ppm CO 2 increased nitrogen fixation rates 1.5-to 3-fold compared to ambient CO 2 in the marine cyanobacterium Trichodesmium. 63,64 Still, experiments carried out here did not rule out enhanced nitrate uptake at elevated CO 2 . Irrespective, the addition of waste CO 2 from industry, electricity or heat generation to an Azolla production system is thus expected to boost biomass productivity with no reduction of protein content.…”
Section: Nitrogen and Protein Content In Azolla Biomassmentioning
confidence: 69%
“…b; Wald‐type z ‐test = 5.33, df = 1, p < 0.001), so meta‐analyses were performed on microalgae only as consumers had too few measurements for separate analyses. Microalgal growth increased under elevated CO 2 conditions, which is consistent with predictions (Xia and Gao ; Chinnasamy et al ; Low‐Decarie et al ). Growth response to elevated CO 2 was positively affected by nitrogen levels and by phosphate levels (Fig.…”
Section: Resultssupporting
confidence: 90%
“…While no differences in vegetative cell production between the CO 2 or temperature treatments were observed at the end of the experiment, this was probably due to all mesocosms converging on a stationary growth phase under the different temperature treatments at the end of the experiment. Previous studies demonstrated that CO2 can have a beneficial effect on N fixation at elevated temperatures for marine species [28], yet we suggest that the stimulatory effect of CO2 on N fixation is growth stage dependent, which is influenced by temperature. We observed the most significant difference in N fixation under CO2 conditions at lower temperatures likely because these cultures experienced a longer (slower, cumulative effect) exponential growth phase than warmer treatments.…”
Section: Discussionmentioning
confidence: 72%